2016
DOI: 10.14687/jhs.v13i3.3923
|View full text |Cite
|
Sign up to set email alerts
|

Domestic violence impact on adolescents<p>Aile içi şiddetin ergenler üzerindeki etkisi

Abstract: Objcective: This research was performed in order to evaluate the effects on adolescents of witnessing intrafamilial violence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 1 publication
2
10
0
Order By: Relevance
“…Moreover, adolescence is a period during which individuals can less tolerate frustration and have difficulty in keeping negative feelings under control. It has been reported that tendency for violence was more intense during this period and the number of adolescents who committed violence has increased day by day (Ayhan & Özkan, 2016; Gençoğlu et al, 2014; Haskan & Yıldırım, 2012). In this study, the mean score of the students from tendency for violence was determined to be 43.95 ± 11.07.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…Moreover, adolescence is a period during which individuals can less tolerate frustration and have difficulty in keeping negative feelings under control. It has been reported that tendency for violence was more intense during this period and the number of adolescents who committed violence has increased day by day (Ayhan & Özkan, 2016; Gençoğlu et al, 2014; Haskan & Yıldırım, 2012). In this study, the mean score of the students from tendency for violence was determined to be 43.95 ± 11.07.…”
Section: Discussionmentioning
confidence: 94%
“…It was also detected that students who were studying at upper grades, whose age group was older in parallel to grade level, whose mothers were employed, whose fathers had less education than a primary graduate, whose incomes were less than their expenses, and who experienced domestic violence showed significantly more tendency for violence. In the literature, studies showed that violence trends of students are at a moderate level and that factors such as gender, parental education level and employment status, family income level, being the first child, number of siblings, and exposure to domestic violence affect students’ tendency to violence (Altın et al, 2017; Ayhan & Özkan, 2016; Gençoğlu et al, 2014). It is thought that sociocultural and demographic structure of society was effective in the emergence of tendency for violence.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations